Peningkatan Ketahanan dan Daya Tarik Keripik Singkong Posyandu Alamanda - Agustina Agustina; Andirantony Andirantony; Jessika Jessika; Jhon Carlie; Julinda Julinda; Nick Feehily; Nova Susanti; Rosni Rosni; Ryo Kusnadi; Vira Debora (National Conference for Community Service Project (NaCosPro), 2019)
The Purpose of Our Social Activities is to make an improvement on-chip packaging with technology such as machines and package designing. The second goals are to help improve the economy of the people in the local area. For the implementation method, we are planning to understand the main problem of their business, after it we observe what we need to make the improvement after we know what we can do, we implement it. The result of the activities was the chips become more interesting and durable while also improves their economy.